A novel interconnector design of SOFC. (7th August 2020) - Kong, Wei; Han, Zhen; Lu, Siyu; Gao, Xiang; Wang, Xiaorong
Abstract: In this study, a novel interconnector design is proposed, which is named as the X-type interconnector. The solid oxide fuel cell (SOFC) models are established for the conventional interconnector and the X-type interconnector. The results indicate that the design of the X-type interconnector is beneficial to the transport of gas in SOFC, which has a higher oxygen concentration under rib than that of the conventional interconnector. Furthermore, compared with the X-type interconnector, the potential difference in cathode is larger for the conventional interconnector, which indicates that the X-type interconnector reduces the current path and improves the performance of SOFC. For any porosity and conductivity of anode and cathode, the X-type interconnector is superior to the conventional interconnector. Moreover, when the cathode conductivity is smaller, the advantage of the X-type interconnector becomes more remarkable.